2020
DOI: 10.1186/s13058-020-01266-x
|View full text |Cite
|
Sign up to set email alerts
|

High hepatocyte growth factor expression in primary tumor predicts better overall survival in male breast cancer

Abstract: Background: Breast cancer is rare in men, but management is focused on tumor characteristics commonly found in female breast cancer. The tumor microenvironment of male breast cancer is less well understood, and insight may improve male breast cancer management. The hepatocyte growth factor (HGF)/c-MET axis and the stromal cell-derived factor-1 (CXCL12)/C-X-C chemokine receptor type 4 (CXCR4) axis are prognostic in women with breast cancer. We aimed to investigate these factors in male breast cancer and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The study of 720 MBCs studying hepatocyte growth factor (HGF) and CXCL12 expression in tumour tissue by Qiu et al observed that high HGF expression in tumour cells was an independent predictor for better OS in nonmetastatic setting (13.0 years compared to 7.5 years in HGF low expressing tumours). High expression of CXCL12 in cytoplasm of tumour cells was also associated with better OS [25].…”
Section: Prognosismentioning
confidence: 88%
See 1 more Smart Citation
“…The study of 720 MBCs studying hepatocyte growth factor (HGF) and CXCL12 expression in tumour tissue by Qiu et al observed that high HGF expression in tumour cells was an independent predictor for better OS in nonmetastatic setting (13.0 years compared to 7.5 years in HGF low expressing tumours). High expression of CXCL12 in cytoplasm of tumour cells was also associated with better OS [25].…”
Section: Prognosismentioning
confidence: 88%
“…The median H-score (<20% difference in percentage) for CXCL12 expression was 100 both in cytoplasm and in nucleus. The median H-score for HGF expression was 106 [25].…”
mentioning
confidence: 99%
“…Also two separate meta-analyses examining the prognostic value of c-MET overexpression by a variety of RNA and protein-based detection methods concluded that c-MET overexpression is associated with both breast cancer recurrence and overall survival [32,33]. In contrast, a large Dutch male breast cancer cohort (n = 841) found that HGF protein expression (as measured by immunohistochemistry) was protective against overall survival [34]; however, this population is quite distinct and male breast cancer is predominantly of luminal subtype, which we found to have lower prevalence of HGF expression [34,35]. Our results add important new data based on a large, diverse study population.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using SPSS version 19 software (IBM Corp.) and data are presented as the mean ± SEM. Survival rate analysis was analyzed using the Kaplan-Meier method, with a log-rank test used for comparison ( 20 ). Statistical differences between groups were determined using a one-way ANOVA, followed by a Student-Newman-Keuls test for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%